PAX2 Mutation-Related Renal Hypodysplasia: Review of the Literature and Three Case Reports - Chang, Yu-Ming; Chen, Chih-Chia; Lee, Ni-Chung; Sung, Junne-Ming; Chou, Yen-Yin; Chiou, Yuan-Yow (Frontiers in Pediatrics, 2022)
Paired box 2 (PAX2)-related disorder is an autosomal dominant genetic disorder associated with kidney and eye abnormalities and can result in end stage renal disease (ESRD). Despite reported low prevalence of PAX2 mutations, the prevalence of PAX2 related disorders may have been underestimated in past studies. With improved genetic sequencing techniques, more genetic abnormalities are being detected than ever before. Here we report three patients from two families with PAX2 mutations identified within one year. Two patients were adults with chronic kidney disease and were followed for decades without correct diagnoses, including one with ESRD who had even undergone kidney transplant. The third patient was a neonate in whom PAX2-related disorder manifested as oligohydramnios, coloboma and renal failure that progressed to ESRD within one year after birth. The phenotypes of PAX2 gene mutation were shown to be highly variable, even within the same family. Early detection promoted genetic counseling and guided clinical management. The appropriate time point for genetic study is an important issue. Clinicians must be more alert for PAX2 mutation when facing patients with congenital kidney and urinary tract anomalies, chronic kidney disease of unknown etiology, involvement of multiple systems and/or a family history of renal disease.